1995
DOI: 10.1128/jb.177.3.723-732.1995
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure and functional analysis of the lysis genes of Lactobacillus gasseri bacteriophage phi adh

Abstract: The lysis genes of the Lactobacillus gasseri bacteriophage adh were isolated by complementation of a lambda Sam mutation in Escherichia coli. Nucleotide sequencing of a 1,735-bp DNA fragment revealed two adjacent coding regions of 342 bp (hol) and 951 bp (lys) in the same reading frame which appear to belong to a common transcriptional unit. Proteins corresponding to the predicted gene products, holin (12.9 kDa) and lysin (34.7 kDa), were identified by in vitro and in vivo expression of the cloned genes. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 78 publications
8
56
0
Order By: Relevance
“…However, permeabilization of the plasma membrane by chloroform upon expression of the lysA gene resulted in immediate lysis. These observations are consistent with other studies, in which the overexpression of phage lysins in the absence of the respective holin functions does not inhibit E. coli growth unless chloroform has been added (3,15). These results suggest that ORF2 encodes a lysin with mureinolytic activity that is functional in E. coli.…”
Section: Fig 2 (A)supporting
confidence: 82%
See 1 more Smart Citation
“…However, permeabilization of the plasma membrane by chloroform upon expression of the lysA gene resulted in immediate lysis. These observations are consistent with other studies, in which the overexpression of phage lysins in the absence of the respective holin functions does not inhibit E. coli growth unless chloroform has been added (3,15). These results suggest that ORF2 encodes a lysin with mureinolytic activity that is functional in E. coli.…”
Section: Fig 2 (A)supporting
confidence: 82%
“…The holin is a hydrophobic membrane protein that forms pores or lesions in the cell membrane through which the murein hydrolase is released to the periplasm and gains access to the peptidoglycan substrate. Such a dual-component lysis system has recently been discovered in many bacteriophages of both gram-negative and grampositive bacteria (15,17,22,25,27,32). The synthesis of the bacteriophage holin (protein S) is tightly controlled at the transcriptional, translational, and posttranslational levels because it determines the time of lysis.…”
mentioning
confidence: 99%
“…Growth and viability of the recombinant strain E. coli JM109 (pMP302) was not affected, even after the addition of 2 % CHCl 3 (data not shown). It has been shown for other phages that expression of a bacteriophage lysin gene in E. coli causes cellular lysis after permeabilization of the plasma membrane with chloroform (Chandry et al, 1997;Henrich et al, 1995); this effect is also observed with the lysin LysA of mycobacteriophage Ms6 (Garcia et al, 2002). The result indicates that LysB is not an additional endolysin.…”
Section: Cloning and Expression Of The Lysb Genesupporting
confidence: 58%
“…They are detailed in the remaining paragraphs according to their functional category. Structural genes Structural proteins (Chung et al, 1991 ;Kim & Batt, 1991a) (Lubbers et al, 1995), origin of replication (Waterfield et al, 1996), lysogeny (Nauta et al, 1996) (Johnsen et al, 1996 ;Johnsen et al, 1995 ;Pedersen et al, 2000), replication (Ostergaard et al, 2001), lysogeny (Breuner et al, 1999 ;Christiansen et al, 1996) (Kakikawa et al, 1996), lysis (Oki et al, , 1996 phi adh Lactobacillus gasseri AJ131519* Lysis (Henrich et al, 1995), structural proteins and origin of replication (Altermann et al, 1999) …”
Section: Database Similarity Searches For Assignment Of Putative Funcmentioning
confidence: 99%